Analisis Penerapan Metode Discussion Dan Role Playing Untuk Meningkatkan Prestasi Belajar Mahasiswa Pada Mata Kuliah Manajemen Kinerja - Susi Handayani; Hasrudy Tanjung (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This study aims to analyze the influence of the application of discussion and role playing methods in the performance management class, whether more effective than the lecture method previously used by most students. This is because the old method is considered less effective and does not get optimal results. Visually the students tend to be less immature in learning, less expressive and less terganli abilities inidividunya. This research is expected to provide new colors for students and teachers, so that will make students become more creative and passionate in learning so that learning achievement will become better. This research will also help to increase the self-reliance, self-confidence and competitive spirit of the students because the method is applied more interactively, involving both parties ie students and lecturers and the ability to work together in groups so far from monotonous impression. This research is a classroom action research, designed specifically in its application and adapted to the syllabus and lecture unit units agreed upon by the institution. The results of the study was as expected although not maximal, the increase in student achievement has been seen with the results of tests conducted by researchers. Student behavior is also seen there are changes, more confident, creative, better tolerance, cooperative and more independent.